2002
DOI: 10.1001/archopht.120.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Follow-up for Scleral Buckling

Abstract: To the report 20-year follow-up data for patients receiving a scleral buckle for treatment of a primary rhegmatogenous retinal detachment (RRD).Methods: Nonconsecutive, retrospective case series. We identified 227 eyes with primary RRD who were treated with a scleral buckle, and for whom at least 20 years of follow-up data were available. Results were classified into 3 subgroups: retina reattached with 1 procedure; retina reattached with 1 or more additional vitreoretinal procedures; or retina detached at 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 8 publications
4
55
1
6
Order By: Relevance
“…Postoperative VA, metamorphopsia, and stereopsis Some studies suggested that scleral buckling and vitrectomy surgery, which anatomically corrects RRD, do not restore visual function, as measured by VA. [12][13][14] In our study, after scleral buckling or vitrectomy to correct RRD, postoperative VA improved significantly compared with preoperative VA in agreement with previous studies. [14][15][16] Scholars suggested that preoperative VA was the key to determine postoperative visual recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Postoperative VA, metamorphopsia, and stereopsis Some studies suggested that scleral buckling and vitrectomy surgery, which anatomically corrects RRD, do not restore visual function, as measured by VA. [12][13][14] In our study, after scleral buckling or vitrectomy to correct RRD, postoperative VA improved significantly compared with preoperative VA in agreement with previous studies. [14][15][16] Scholars suggested that preoperative VA was the key to determine postoperative visual recovery.…”
Section: Discussionsupporting
confidence: 91%
“…It may be that selecting eyes with symptomatic retinal detachments of more limited extent (anterior to the equator) that are smooth and shallow, as in the study by Vrabec and Baumal, 3 produces better results. Certainly, for eyes with symptomatic retinal detachments the failure rate of 5/13 (38.5%) is rather high in our study and higher than published rates of pneumatic retinopexy, 16 scleral buckling, 17,18 or pars plana vitrectomy. 19 However, in patients who are apprehensive of invasive surgery or for patients who may be infirm and poor surgical candidates (eg unable to lay flat due to severe emphysema, heart failure, or severe kyphosis) or who do not have the resources for operative repair (lack of ophthalmologist trained in scleral buckling or vitrectomy) DLP may represent a good option.…”
Section: Discussioncontrasting
confidence: 66%
“…Numerous studies have been published recommending one of the two methods [1,4,13,14,20,24,26,27,29,30,32]. We could identify no consensus among several editorial comments on this issue [6, 15-18, 33, 34].…”
Section: Discussionmentioning
confidence: 93%